Robust 3D-trapezoid composite fabric withstanding repeat impact/compression for personal protection. (1st October 2021) - Cai, Fei; Gao, Shuang; Bao, Yanling; Sun, Jintao; Si, Yinsong; Fu, Yaqin
Abstract: Personal protective material against low-speed impact is highly needed in daily life. 3D-trapezoid composite fabrics with excellent impact resistance were prepared by impregnating and coating a 3D-trapezoid fabric in the spacer layer and the surface layer respectively, using hollow glass microspheres (HGMs) as reinforcement and waterborne polyurethane (WPU) as matrix. HGMs can significantly improve the impact strength of the fabric from 9.87 KJ/m 2 to 23.08 KJ/m 2 . Smaller HGMs contribute greater to the impact strength with the same volume fraction, especially when they were impregnated into the spacer layer instead of the surface layer. The synergistic effect of the HGMs and fabric structure was explored and found that imposed impact energy can be expended by surface absorption, elastic deformation, and transmission to impregnated layer. With optimized structure, the 3D-trapezoid composite fabrics withstand repeat impacts and the impact strength is still 2.17 times higher at the 20 th shock. Moreover, high compression strength of 47.23 MPa can also be achieved with an increase of 3.47 times, which is still 3.37 times higher at the 5 th cycle. By combination of HGMs and 3D-trapezoid structure, the composite fabric, demonstrating excellent cushioning function and scratchability, can be a potential wearable protective material against low-speed impact.